2017
DOI: 10.5380/rf.v47i1.44203
|View full text |Cite
|
Sign up to set email alerts
|

PHYSIOLOGICAL AND ENZYMATIC CHANGES DURING SEED MATURATION AND GERMINATION OF Luehea divaricata

Abstract: Luehea divaricata Mart. & Zucc is tree is of great ecological and economic importance. This study investigated the effect of fruit maturation on the germination and vigor of L. divaricata. Fruits were harvested at three maturity stages (unripe or green, brown and open) defined by digital colorimetry and seeds extracted from each stage divided into lots of earliest harvested and stored. Germination test was conducted with four replicates of 25 seeds from each fruit maturity stage in plastic boxes under temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…However, after 28 days, seed germination began to increase as moisture decreased, which continued during maturation, suggesting a possible inverse relationship between the aforementioned variables (Figures 3 and 4). The data obtained in this study are corroborated by Schulz et al (2017), who evaluated germination and moisture content of seeds of Luehea divaricata (Malvaceae), a species characterized by dry and dehiscent fruits, as well as A. glazioveana, and concluded that the increase in germination percentage coincided with the reduction in moisture. Furthermore, the high water content in early development of the seeds is linked to the synthesis and metabolism of reserve substances such as proteins, starch, and lipids.…”
Section: Discussionsupporting
confidence: 80%
“…However, after 28 days, seed germination began to increase as moisture decreased, which continued during maturation, suggesting a possible inverse relationship between the aforementioned variables (Figures 3 and 4). The data obtained in this study are corroborated by Schulz et al (2017), who evaluated germination and moisture content of seeds of Luehea divaricata (Malvaceae), a species characterized by dry and dehiscent fruits, as well as A. glazioveana, and concluded that the increase in germination percentage coincided with the reduction in moisture. Furthermore, the high water content in early development of the seeds is linked to the synthesis and metabolism of reserve substances such as proteins, starch, and lipids.…”
Section: Discussionsupporting
confidence: 80%
“…Seeds removed from fruits that were on the ground, bright red fruits and yellow fruits with red spots exhibited the highest germination speed index, with a mean of 1.02, not different from one another. Evaluating the effect of physiological maturation on the germination of Luehea divaricate, Schulz et al (2017), observed that the germination speed index was highest in seeds obtained from fruits with green coloration than that of brown fruits. Brown-colored fruits corresponded to a stage of maturation more advanced than the that of fruits with green coloration.…”
Section: Experiments Imentioning
confidence: 99%
“…A. C. Smith (LOPES; NÓBREGA; MATOS, 2014); Luehea divaricata Mart. (SCHULZ et al, 2017); e Parapiptadenia rigida (Benth.) Brenan (BRAZ et al, 2018).…”
Section: Introductionunclassified